PEMBUATAN KOMPOSIT INTERPENETRASI JARINGAN POLIMER ANTARA POLIURETAN-KARET ALAM SIR-10 DENGAN PENAMBAHAN MONTMORILLONIT SEBAGAI BAHAN PENGISI - Supran Hidayat Sihotang; Wilda Wahyuni Siregar; Dwi Handayani (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2019)
The using of polyurethane (PU) that was added simultaneously with SIR-10 natural rubber (NR) as a synthesis of interpenetrating polymer network (IPN) which was then added montmorillonit (MMT) as filler material in the composite forming process IPN. Polypropylene glycol and toluene are diisocyanate with a comparison of the number of moles between NCO: OH = 2:1, which was used to synthesize a derived from PU. In advance stearic acid, zinc oxide, MBTS, and sulfur are added as a revulzation of NR. PU and NR vulcanization combined to produce IPN NR-PU by using temperature of 140 oC. The addition of MMT in the IPN NR-PU will generate the IPN NR-PU-MMT composite. Furthermore, the IPN NR-PU-MMT composite was characterised with tensile strength test, water absorption test, SEM and DSC. The results of this research showed that the composite mixture of IPN increased with the increase of MMT to the optimum limit in comparison between NR-PU and MMT was 74 phr: 26 phr was a mixture that produced good tensile strength and properties of ductility are good. The mechanical, physical, and morphological properties of the IPN are influenced by the number of MMT that was used to produce components that cross each other in the bonding interface.